The influence of the preparation of polyphenols and diazepam on behavioral reactions and sanogenesis at the dosed traumas of the gingival margin of one year’s rats - Nikolaeva, Anna Vladimirovna (Pedagogy and Psychology of Sport, 2016)
At the experiments on the 22 rats, 12 months age was studied the influence of the preparation of Phytosedum polyphenols and the tranquilizer of Diazepamum on the healing process of the standart injuries of gums. The assessment of behavioral responses was carried out for 5 minutes in rats in the test "open field" - were registered parameters, that describing their motor activity. The Aim of this research was to study the influence of the preparation of polyphenols on the healing process of the standard injuries of the mucous membrane gingiva depending on the type of conduct and the usefulness of the diet of old rats. Materials and methods. In the experiment were used 22 albino rats of 12 months of age. Before starting the experiment was evaluated the behavioral responses of all animals in the test "open field." Then rats were randomly divided into 4 groups, which daily orally administered: 1st group (5 rats) - water (1.0 ml / kg); 2d group (5 rats) - water - 1.0 ml / kg; 3rd group (6 rats) "BDP + diazepam"; 4th group (6 rats) - ("BDP + phytosedum " - 1.0 ml / kg in 1: 1 dilution). Results and conclusions. Established the dependence the rate of the occurrence of complete healing of injuries from "psycho" rats. In terms of total active motor and search activity of rats healing occurs earlier than in passive animals. The introduction of drugs of natural origin - fitoseda and synthetic - of Diazepamum offsetting these differences. Diazepam lowerd terms of the full adhesion, and Phytosedum - stimulate of the process of sanogenesis fitosed. Despair reduction of research and the behavioral activity of old rats from the usefulness of their diet.